Bibliometric Analysis: Research on the Utilization of Herbal Plant Extracts for Wound Treatment - Prasetyo, Sigit Nian; Soesanto, Edy; Redjeki, Sri; Pranata, Satriya (Babali Publisher, 2024)
Background: Herbs have been widely used in treating and managing various types of wounds. This study aims to analyze the research scope of utilizing herbal plant extracts for wound treatment. Methods: The method used in this study is to search for articles using the Dimensions application published from 2015-2023. Research is limited by selecting categories: Biomedical and clinical sciences, Biological sciences, Agricultural, Veterinary and Food sciences, and Pharmacology and Pharmaceutical sciences. The keywords used are